The secularization of baptism: how Baptists took God out of baptism, and how to fix the problem - MacKim, Mark G. (McMaster theological studies series, 2025)
Does God actually do anything in baptism? Is it more than just a symbol? Most early Baptists would have answered "yes." Most Baptists today would answer "no." How and why did this change happen--and does it matter? Providing thorough documentation of the changing understandings of baptism among American, Canadian, and English Baptists from the 1600s to the present day, The Secularization of Baptism demonstrates that four factors led to the symbolic-only position becoming dominant. These were suspicion, in reaction to Roman Catholicism, of the idea of God revealing himself through the physical; the influence of the Enlightenment (and "embarrassment" with claims that God could be acting in the world today); reaction against the Oxford Movement; and reaction against the understanding of baptism advocated by the Disciples of Christ ("Campbellites"). The now dominant "symbolic-only" position so focuses attention on what the believer is doing in baptism that God is seen as largely absent from, and doing nothing through, the rite; in effect believers' baptism has been secularized. A carefully reasoned biblical and theological argument is made for a return to the Regular/Particular Baptist view that God is both profoundly spiritually present and active in baptism, while at the same time rejecting the "sacramentalist" position advocated by a small number of mid-twentieth and twenty-first century Baptists, such as H. Wheeler Robinson, George Beasley-Murray, Stanley K. Fowler, and Anthony R. Cross